De jure and de facto political power dynamics during the 1997-1998 asian financial crisis: A socio-economic perspective on sustainability in Indonesia and Malaysia - Widianingsih (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: The 1997-1998 Asian Financial Crisis had a profound impact on the economies and governance of many Southeast Asian countries, including Indonesia and Malaysia. The researcher therefore sought to examine the interaction between de jure and de facto political forces that shaped Indonesia & Malaysia's crisis management strategies and institutional reforms. The study highlights the entrenched power of authoritarian leaders with the influence of business elites determining policy responses and the level of public trust. Methods: This research model uses a comparative qualitative study method, analyzing secondary sources such as literature, policies, and historical records. The researcher identifies patterns and differences in governance, economic policies, and institutional responses in both countries, providing an in-depth understanding of the political dynamics and power structures that influence crisis outcomes and impacts. Findings: The 1997-1998 Asian Financial Crisis was caused by liquidity issues, capital inflows, and institutional weaknesses. Indonesia and Malaysia's economic growth was based on fragile foundations, with crony capitalism and power imbalances contributing to the crisis. Addressing power structures, promoting openness, and adopting democratic values are crucial for long-term resilience and fairness. Malaysia implemented capital controls and maintained political stability under the leadership of Mahathir Mohamad, Indonesia's dependence on International Monetary Fund (IMF) assistance and widespread public discontent led to Soeharto's resignation and a shift towards democratization. In other words, the findings underscore the important role of political power dynamics in shaping economic and institutional resilience and provide valuable insights into the governance challenges of non-democratic regimes during crises. Conclusion: The study concludes that the contrasting crisis management strategies of Indonesia and Malaysia during the 1997-1998 Asian Financial Crisis were significantly influenced by the interplay of authoritarian political power and business elite interests. Novelty/Originality of this article: This research offers new insights by exploring how authoritarian power dynamics and the influence of business elites affect the policy strategies adopted, the level of political stability and public trust in both countries.